Electron-Transfer Acceleration Investigated by Time Resolved Infrared Spectroscopy - Vlček, Antonín; Kvapilová, Hana; Towrie, Michael; Záliš, Stanislav (Accounts of chemical research, 2015)
Ultrafast electron transfer (ET) processes are important primary steps in natural and artificial photosynthesis, as well as in molecular electronic/photonic devices. In biological systems, ET often occurs surprisingly fast over long distances of several tens of angströms. Laser-pulse irradiation is conveniently used to generate strongly oxidizing (or reducing) excited states whose reactions are then studied by time-resolved spectroscopic techniques. While photoluminescence decay and UV–vis absorption supply precise kinetics data, time-resolved infrared absorption (TRIR) and Raman-based spectroscopies have the advantage of providing additional structural information and monitoring vibrational energy flows and dissipation, as well as medium relaxation, that accompany ultrafast ET. We will discuss three cases of photoinduced ET involving the ReI(CO)3(N,N) moiety (N,N = polypyridine) that occur much faster than would be expected from ET theories. [Re(4-N-methylpyridinium-pyridine)(CO)3(N,N)]2+ represents a case of excited-state picosecond ET between two different ligands that remains ultrafast even in slow-relaxing solvents, beating the adiabatic limit. This is caused by vibrational/solvational excitation of the precursor state and participation of high-frequency quantum modes in barrier crossing. The case of Re–tryptophan assemblies demonstrates that excited-state Trp → *ReII ET is accelerated from nanoseconds to picoseconds when the ReI(CO)3(N,N) chromophore is appended to a protein, close to a tryptophan residue. TRIR in combination with DFT calculations and structural studies reveals an interaction between the N,N ligand and the tryptophan indole. It results in partial electronic delocalization in the precursor excited state and likely contributes to the ultrafast ET rate. Long-lived vibrational/solvational excitation of the protein ReI(CO)3(N,N)···Trp moiety, documented by dynamic IR band shifts, could be another accelerating factor. The last discussed process, back-ET in a porphyrin–ReI(CO)3(N,N) dyad, demonstrates that formation of a hot product accelerates highly exergonic ET in the Marcus inverted region. Overall, it follows that ET can be accelerated by enhancing the electronic interaction and by vibrational excitation of the reacting system and its medium, stressing the importance of quantum nuclear dynamics in ET reactivity. These effects are experimentally accessible by time-resolved vibrational spectroscopies (IR, Raman) in combination with quantum chemical calculations. It is suggested that structural dynamics play different mechanistic roles in light-triggered ET involving electronically excited donors or acceptors than in ground-state processes. While TRIR spectroscopy is well suitable to elucidate ET processes on a molecular-level, transient 2D-IR techniques combining optical and two IR (or terahertz) laser pulses present future opportunities for investigating, driving, and controlling ET.